Navigating a new school - Meyer, Terry Teague (New York : Rosen Central, 2013)
Offers advice to students that are starting at middle school, covering transportation, lockers, social life, staying safe, and more.
Includes bibliographical references (p. 55-61) and index.
6.6
5-8.
5-8
Keywords: Articulation (Education) -- United States -- Juvenile literature; First day of school -- United States -- Juvenile literature; Middle school students -- United States -- Juvenile literature; Middle schools -- United States -- Juvenile literature; Articulation (Education); First day of school; Middle school students; Middle schools; Articulation (Education); First day of school; Middle school students; Middle schools